Analysis Of Intention Of Professional Students To Become Livestock Business Entrepreneurs In Tamil Nadu - Kumar, G. Senthil; Subramonian, B. Suresh; Gnanaraj, P. Tensingh; Pandian , A. Serma Saravana; Varathan , B. Jaya (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
A study was undertaken to analyze the intention of professional students to become Livestock Business Entrepreneurs in Tamil Nadu. The data for the present study was collected from third year students of Madras Veterinary College, Chennai and Institute of Food and Dairy Technology, Koduvalli. It was observed that the more than three fourth (76.47 per cent) of the sample respondents were willing to start livestock business. Course-wise analysis showed that the willingness to start livestock business was more among B.Tech (FPT) students compared to B.V.Sc. & A.H students. Gender-wise analysis indicated that Boys were more willing to become livestock entrepreneur (84.85 per cent) than girls (61.11 per cent). Locality-wise analysis of entrepreneurial intention among the sample respondents explained that 83.33 per cent of respondents from rural locality and 72.73 per cent of respondents from urban locality were willing to start livestock business. The community-wise analysis indicated that the willingness to start livestock business was more among OC (100 per cent), followed by SC (81.25 per cent), BC (72.00 per cent) and MBC (60.00 per cent).